Recurrent Renal Cell Carcinoma with Synchronous Tumor Growth in Azygoesophageal Recess and Duodenum: A Rare Cause of Anemia and Upper Gastrointestinal Bleeding - Vamshidhar R. Vootla; Muhammad Kashif; Masooma Niazi; Suresh K. Nayudu (Case Reports in Oncological Medicine)
Renal cell carcinoma (RCC) has potential to present with distant metastasis several years after complete resection. The common sites of metastases include the lungs, bones, liver, renal fossa, and brain. RCCs metastasize rarely to the duodenum, and duodenal metastasis presenting with acute gastrointestinal bleed is infrequently reported in literature. We present a case of synchronous presentation of duodenal and azygoesophageal metastasis manifesting as acute upper gastrointestinal bleeding, four years after undergoing nephrectomy for RCC. The patient underwent further workup and was treated with radiation. The synchronous presentation is rare and stresses the importance of searching for recurrence of RCC in patients presenting with acute gastrointestinal bleeding.